Towards a disable–friendly, energy–efficient and sustainable green campus - Salleh, Md. Noor; Al-Mamun, Abdullah; Eusuf, Muhammad Abu; Mohd Amin, Ruzita; Alam, Md. Zahangir; Ahmed, Musse Mohamud (2016)
Several initiatives are taken in order to improve the amenities for the improved accessibility to the disable people at the International Islamic University Malaysia (IIUM) Gombak Campus. Efforts on the energy efficiency, resource management, conversion of wastes into value-added products, reducing the effect of natural calamity and other accidental hazards are being continued to ensure safe and comfortable living in the campus. In order to make the system more feasible and sustainable, most of the time, internal human capital and financial resources are utilised to improve operation and maintenance of the green campus. This paper is mainly intended to share the experiences at IIUM in order to reduce operation cost but improve the quality of the campus life.